2015
DOI: 10.1093/jmcb/mjv011
|View full text |Cite
|
Sign up to set email alerts
|

Function coupling of otoferlin with GAD65 acts to modulate GABAergic activity

Abstract: Otoferlin, an integral membrane protein implicated in a late stage of exocytosis, has been reported to play a critical role in hearing although the underlying mechanisms remain elusive. However, its widespread tissue distribution infers a more ubiquitous role in synaptic vesicle trafficking. Glutamate, an excitatory neurotransmitter, is converted to its inhibitory counterpart, γ-aminobutyric acid (GABA), by L-glutamic acid decarboxylase (GAD), which exists in soluble (GAD67) and membrane-bound (GAD65) forms. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…A recent study concluded that otoferlin both directly interacts with glutamate decarboxylase (GAD) and affected GAD transcript levels (Sarro et al 2008;Noh et al 2010;Wu et al 2015). We therefore measured GAD and GABA receptor subunit expression levels in WT and mutant larvae (Figure 8).…”
Section: Otofb Mutants Display Abnormal Transcript Levels Of Gabar Subunits and Gadmentioning
confidence: 99%
“…A recent study concluded that otoferlin both directly interacts with glutamate decarboxylase (GAD) and affected GAD transcript levels (Sarro et al 2008;Noh et al 2010;Wu et al 2015). We therefore measured GAD and GABA receptor subunit expression levels in WT and mutant larvae (Figure 8).…”
Section: Otofb Mutants Display Abnormal Transcript Levels Of Gabar Subunits and Gadmentioning
confidence: 99%
“…Inactivation of either of these genes results in profound deafness (Platzer et al 2000;Roux et al 2006). Otoferlin has been detected in several brain regions, including hippocampal neurons expressing GAD65, a marker of inhibitory neurons (Roux et al 2006;Wu et al 2015), but no functional deficit has yet been characterized in the brains of any of the GABA/glycinergic to purely glycinergic transmission of MNTB neurons (Hirtz et al 2011(Hirtz et al , 2012Satheesh et al 2012).…”
Section: A) the Auditory Ribbon Synapsementioning
confidence: 99%
“…Firstly, these cell cultures are mostly composed of cells with cholinergic characteristics (Kovalevich & Langford, 2013). However, both GABAergic and glutamatergic systems have been previously explored in these cultures (Kim et al, 2008;Lu et al, 2009;Mendell et al, 2018;Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%